A study on the identification, quantification, and biological activity of compounds from Cornus officinalis before and after in vitro gastrointestinal digestion and simulated colonic fermentation. (November 2022) - Fan, Shucong; Li, Jianan; Zhang, Xiaojuan; Xu, Dingqiao; Liu, Xiang; Dias, Alberto C.P.; Zhang, Xiaoying; Chen, Chen
Graphical abstract: Highlights: The content of phenolic compounds was increased during simulated digestion. The antioxidant activity increased of C. officinalis after simulated digestion. The α-amylase inhibitory activity increased of C. officinalis after small intestine. Provide more reasonable guidance for consumers' diet. Provided theoretical basis for the development of C. officinalis functional foods. Abstract: This study aimed to investigate the changes in chemical composition content, and biological activity of Cornus officinalis before and after simulated digestion in vitro. The results showed that the iridoid glycosides in C. officinalis were less stable than phenols in the gastrointestinal digestion stage. After colonic fermentation simulation, iridoid glycosides were almost completely decomposed. However, the content of phenolic compounds was significantly increased, especially the contents of gallic acid, catechin, epicatechin, and benzoic acid. Moreover, after colonic fermentation, the antioxidant activity significantly increased and the antioxidant activity of the GI tract and after colonic fermentation increased by 9.45 % and 79.15 %, respectively, compared with undigested antioxidant activity. It is also found that the α-amylase inhibitory activity of C. officinalis was significantly increased in the small intestine, which was 719.57 % higher than that of the undigested ones. The results provided a theoretical basis for the development of C. officinalis derived functional foods.